Using Waste Asphalt Concrete (WAC) for Improving Poorly sandy Graded (PSG) Subgrade Soil - Khawla H. H. Shubber, Asst. Prof. Dr.; Ali S. M. Alkizwini, Eng. (International Journal of Engineering and Technology, 2018)
Waste asphalt concrete (WAC) is one of main current sustainable problems facing accumulation in high quantities as a result of the highways failure, maintenance and reconstructions. On the other hand, presence of large amounts of poorly sand graded (PSG) soil near rivers, which are not suitable in case of using it as subgrade soil. So, present research focusing on study the effect of adding WAC on the properties of PSG soil. Modified Procter test, California Bearing Ratio test (CBR), Direct Shear test were depend on evaluating the stabilized soil properties (i.e. dry density, optimum water content, CBR, and direct shear).Â  PSG river soil used as subgrade soil in this research brought from sides of Sadit AL- Handayi in Babylon Governorate located in middle west of Iraq, about 60 km south west of Baghdad, capital of Iraq. Percent of adding are (12, 24, 36, and 48)% by weight. Results showed that the adding of WAC increase the dry density in different rate. While the optimum water content decrease with increasing WAC added. Direct shear of stabilized soil increase while angle of internal friction decrease with increasing of added WAC. CBR values increase with increasing WAC added.Â Â